Homer and Langley [compact disc, unabridged] : a novel - Doctorow, E. L., 1931-2015 (Random House Audio, 2009)
Bronx-born E. L. Doctorow - who attended Kenyon College, served with the Army of Occupation in Germany, and penned his first novel after perusing a plethora of Western genre scripts as a reader in Hollywood - presents his thirteenth full-length novel, Homer and Langley. Other critically acclaimed works by Doctorow include Ragtime; City of God; and The March.